CONSORT-Independent prognostic value of asphericity of pretherapeutic F-18 FDG uptake by primary tumors in patients with breast cancer. Issue 46 (November 2017) - Jung, Ji-hoon; Son, Seung Hyun; Kim, Do-Hoon; Lee, Jeeyeon; Jeong, Shin Young; Lee, Sang-Woo; Park, Ho Yong; Lee, Jaetae; Ahn, Byeong-Cheol
Abstract: Background: The aim of this study was to evaluate the prognostic implication of asphericity (ASP); spatial irregularity; of pretherapeutic 18 F 2-deoxy-2-fluoro-D-glucose ( 18 F FDG) tumor uptake in patients with invasive ductal carcinoma (IDC) of the breast. Methods: One hundred thirty-one female IDC patients (mean age = 48.1 ± 10.4 years), with pathological tumor size greater than 2 cm were retrospectively evaluated using 18 F FDG positron emission tomography/computed tomography (PET/CT). ASP of 18 F FDG distribution was calculated on the basis of the deviation of the tumor shape from spherical symmetry. Progression-free survival (PFS) was predicted on the basis of the univariate and multivariate analyses of the measured clinicopathologic factors and metabolic PET parameters [maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG)]. Results: The PFS rate among the 131 patients was 90.1%. The mean follow-up time was 50 months for the entire study cohort and 26 months for the patients with recurrent disease. It is evident from the univariate analysis that N stage, hormonal receptor (Estrogen, ER/Progesterone, PR) status, MTV (⩽4.2 mL), and ASP (⩽15.1%) affected the PFS. Hazard ratios (HRs) estimated from the multivariate Cox regression analysis show that N stage (HR = 17.6), ASP (HR = 11.9), and hormonal receptor status (HR = 6.9) were independent prognostic factors in predicting PFS. In the subgroup of patients with lymph node metastasis, ASP (HR = 10.9) and hormonal receptor status (HR = 9.1) were independent prognostic factors for PFS. Conclusion: ASP of 18 F FDG uptake is an independent predictor of outcome in IDC patients, and can be used for prognostic stratification.